2012
DOI: 10.1007/s00432-011-1136-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolidase activity, oxidative stress, and nitric oxide levels in patients with bladder cancer

Abstract: ObjectivesProlidase is a member of the matrix metalloproteinase family. It plays a major role in collagen turnover, matrix remodeling and cell growth. Nitric oxide (NO) regulates many processes such as collagen synthesis and matrix remodeling. Thus, NO may augment angiogenesis, tumor invasion, and metastasis. The aim of this study was to investigate total antioxidant status (TAS), malondialdehyde (MDA) and NO levels in patients with bladder cancer and to determine their relationship with prolidase activity.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 40 publications
3
49
0
1
Order By: Relevance
“…Depending on these changes in albumin, serum albumin levels should be considered in IMA studies. Gecit et al (2012), and Badjatia et al (2010) showed increased oxidative stress and increased total anti-oxidant activity in bladder cancer patients. In our study, we found the difference of TAS, TOS and OSI between cancer patients and controls, statistically significant.…”
Section: Discussionmentioning
confidence: 93%
“…Depending on these changes in albumin, serum albumin levels should be considered in IMA studies. Gecit et al (2012), and Badjatia et al (2010) showed increased oxidative stress and increased total anti-oxidant activity in bladder cancer patients. In our study, we found the difference of TAS, TOS and OSI between cancer patients and controls, statistically significant.…”
Section: Discussionmentioning
confidence: 93%
“…This NO stimulates matrix metalloproteinases (MMPs), especially prolidase activity, which is involved in the terminal step of collagen degradation. Significantly higher serum prolidase activities were reported in patients with bladder cancer than healthy controls [155]. Therefore, increased prolidase activity may, in part, play a role in the pathogenesis of bladder cancer.…”
Section: Bladder Cancermentioning
confidence: 91%
“…Serum prolidase activity and oxidative stress parameters NO, MDA levels were detected signifi cantly higher in bladder cancer than in controls, while TAS levels were found signifi cantly lower (32).…”
Section: Oxidative Stress and Prolidasementioning
confidence: 86%